EXPLOITATION OF NATURE AND SPIRITUAL DECADENCE: ETHICAL RESPONSIBILITY IN ISLAM THROUGH RITUAL AND RELIGIOSITY AS THE FOUNDATION OF HUMANITY - Irham Multazam; Binti Khalimatuzzahro; Ahmad Muttaqin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The large-scale exploitation of nature currently occurring in Indonesia reflects a crisis of spirituality among modern humans in their understanding and treatment of nature. The loss of sacred awareness of nature as God's creation has led to an exploitative, rather than participatory, relationship between humans and nature. This study aims to examine the connection between the exploitation of nature and spiritual decadence, as well as how Islamic values can provide a relevant and transformative ecological ethical framework. The method used is a qualitative study with a literature review approach, involving critical analysis of Islamic texts and spiritual ecology theories from thinkers such as Seyyed Hossein Nasr and Roy A. Rappaport. The results of the study show that Islamic principles such as Tawhid, Khilafah, Amanah, and Shari'ah have strong potential to shape spiritual-based ecological awareness. Additionally, rituals in traditional and religious communities also function as ecological and moral mechanisms. In conclusion, the reconstruction of Islamic spiritual values in an environmental context is essential to address contemporary ecological crises, particularly in Indonesia.